Indigenous Futurisms: Transcending Past/Present/Future - Herr, Chelsea; Well-Off-Man, Manuela; Fricke, Suzanne Newman (IAIA Museum of Contemporary Indian Arts, 2020)
Indigenous Futurisms: Transcending Past/Present/Future investigates a major trend in Contemporary Native Art–the rise of futuristic or science-fiction inspired Native American art. The essays and artworks present the future from a Native perspective and illustrate the use of Indigenous cosmology and science as part of tribal oral history and ways of life. Several of the artists use sci-fi related themes to emphasize the importance of Futurism in Native cultures, to pass on tribal oral history and to revive their Native language. However, Indigenous Futurism also offer a way to heal from the traumas of the past and present–the post-apocalyptic narratives depicted in some of the artworks are often reality for Indigenous communities worldwide.
OCLC: 1197536229
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings–from the 1950s onward–by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Section: xiii, 205 pages : illustrations principalement en couleur, portraits ; 27 cm
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé